From Scratch to Plate: “Accounting Information Systems for Spices In Madura Island” - Citra Nurhayati; Nurul Kompyurini; Anita Carolina; Prayudi S Prabowo (Eduvest - Journal of Universal Studies, 2022)
Spices are a priceless wealth of Indonesia. Many other countries in the world import it especially Europeans who desperately need pepper for almost all the flavors of its cuisine. The culinary history of Indonesia is not spared from the raw ingredients of spices that become the main raw materials of Indonesian specialties. Almost all the flavors of cuisine throughout Indonesia use spices as seasoning "Madura" has a typical culinary that also uses spices such as soto, satay, Kaldu, and Nasi serpang. With the proliferation of culinary business in Madura and also the needs of daily cuisine that in fact use spices; This makes the need for spices increase. But with such a wide distribution and widespread spice plantations in Madura, encourage researchers to know the distribution process of the spices after harvesting until it reaches the hands of consumers (from scratch to plate). The distribution process can be explained in more detail by using one of the “Accounting Information System” business processes called "Supply Chain". In the "Supply Chain" will be explained a clear sequence of spices began to be planted-harvested-merchant-consumers. An Accounting Information System framework which is consists of "input-process-outputs". Input can be input or raw materials (spices seeds), while the process are: Spices begin to be planted, maintained then harvested (as output). The Output (harvested Spices) are entering the Chain of “Supply Chain”; they are going to be marketed or distributed to consumers directly, or sent to middle traders, and or sent to the market. The Supply Chain is expected to be able to better known in detail the journey of "The Spice" to reach the consumer to be used as the main spice in cooking, along with the price that occurs and the relationship that occurs between producers, middle parties and consumers. This research was conducted using qualitative methods. The data processing technique by interviewing several important informants Spices are a priceless wealth of Indonesia. Many other countries in the world import it especially Europeans who desperately need pepper for almost all the flavors of its cuisine. The culinary history of Indonesia is not spared from the raw ingredients of spices that become the main raw materials of Indonesian specialties. Almost all the flavors of cuisine throughout Indonesia use spices as seasoning "Madura" has a typical culinary that also uses spices such as soto, satay, Kaldu, and Nasi serpang. With the proliferation of culinary business in Madura and also the needs of daily cuisine that in fact use spices; This makes the need for spices increase. But with such a wide distribution and widespread spice plantations in Madura, encourage researchers to know the distribution process of the spices after harvesting until it reaches the hands of consumers (from scratch to plate). The distribution process can be explained in more detail by using one of the “Accounting Information System” business processes called "Supply Chain". In the "Supply Chain" will be explained a clear sequence of spices began to be planted-harvested-merchant-consumers. An Accounting Information System framework which is consists of "input-process-outputs". Input can be input or raw materials (spices seeds), while the process are: Spices begin to be planted, maintained then harvested (as output). The Output (harvested Spices) are entering the Chain of “Supply Chain”; they are going to be marketed or distributed to consumers directly, or sent to middle traders, and or sent to the market. The Supply Chain is expected to be able to better known in detail the journey of "The Spice" to reach the consumer to be used as the main spice in cooking, along with the price that occurs and the relationship that occurs between producers, middle parties and consumers. This research was conducted using qualitative methods. The data processing technique by interviewing several important informants spread across 4 Regency in Madura which is very helpful in solving problems in the formation of the Supply Chain. across 4 Regency in Madura which is very helpful in solving problems in the formation of the Supply Chain.